Mitigate+ wins grant to scale the application of women’s empowerment measures to climate research - CGIAR Initiative on Low-Emission Food Systems (2023)
The CGIAR GENDER Impact Platform has named the CGIAR Initiative on Low-Emission Food Systems, otherwise known as Mitigate+, as among the awardees of USD100,000 grants to apply women’s empowerment metrics to research on climate change.